Study of the spatio-temporal dynamics of the Ait Daoud ou Ali (Central High Atlas, Morocco) Forest using geospatial techniques - Hili, Aïman; Bissour, Rachid; Jaa, Farid; Reddad, Hanane; El Jouhary, Yassine (Revista de Estudios Andaluces, 2022)
For a long time, Man has been looking for the exploitation of natural resources for daily purposes. Thus, the current scientific and technological development has facilitated and given him real opportunities for the overexploitation of these resources in general and the plant cover in particular. In order to show this exploitation, we want, in this article, to study the evolution of the vegetation cover of the forest of Ait Daoud or Ali, located in the Central High Atlas on an area of 30 860 ha, between 1972, 1999 and 2020, based on remote sensing and GIS tool. Regarding the methodology of work, the multi-chronic study of the dynamics of the vegetation cover of the study area, is based on the spatio-temporal analysis and processing of satellite images by remote sensing space. Indeed, in this paper we have opted for this approach which is based on the use of data from LandSat satellite images of three types; these are the images of type MSS, ETM and Oli, for three dates 1972, 1999 and 2020 (period of 48 years) to identify the spatial differences of the vegetation cover between the three selected dates. Indeed, the study of the dynamics of the vegetation cover of the forest of Ait Daoud or Ali between 1972, 1999 and 2020, showed a very important spatio-temporal variation, linked essentially to several factors (natural and human). The comparison of the results of the classification of Landsat images, showed a decline and a significant degradation of vegetation cover between 1972 and 1999 of 12% of the total area of the study area. This degradation is justified by the intervention of several factors, including climatic conditions and dry periods that Morocco has experienced in this period. For the second period (1999-2020), the treatment showed an increase in vegetation cover of about 10%. In this study, we have highlighted the impact of natural factors and especially anthropic actions on the dynamics of the forest of Ait Daoud or Ali located in the Central High Atlas, based on the use of geospatial techniques that have allowed us to have very precise information on the spatio-temporal dynamics of plant cover.